Flexible Phase Synchronization for Wireless Optical Coherent Communication System With Adaptive Fractionally-Spaced Blind Equalization Combined With Adaptive Kalman Filter - ShuPeng Zhang; LiYing Tan; Jing Ma (IEEE Photonics Journal)
Wireless optical coherent communication can be used as the backbone supporting technology of air-space-ground-sea-integrated network. In wireless optical coherent communication, the information can be demodulated from the carrier correctly only when the phase synchronization is accurate. Operating in different systems and diverse environments presents challenges for phase synchronization, especially lasers with different line-widths and atmospheric turbulence channels that cause scintillation and wave-front distortion. We propose a combination of adaptive fractionally-spaced blind equalization and adaptive kalman filter to realize phase synchronization under different line-widths and different scintillation and wave-front distortion. This combination which changed the limitation that the original settings of each part is not directly applicable to atmospheric channel combines spatial diversity in a natural way, jointly removes amplitude noise and phase noise more thoroughly with the optimal bandwidth, and can realize phase synchronization under time-varying conditions. The signal quality of the proposed scheme with constant parameter output can be improved 1-2dB in both mean square error (MSE) and symbol to error ratio (SER) compared to traditional equal gain combining (EGC) followed by Viterbi-Viterbi phase estimation (VVPE) and the proposed constant parameter scheme has more laser line-width options. The proposed scheme with noise parameter corrected by Autoregressive method outperforms the constant parameter scheme 1-2dB at both MSE and SER and has higher and wider line-width selections. With this design, phase synchronization can be more flexible to adapt to dynamic changes, which will be more suitable for future applications of wireless optical networks with dynamic,noisy, diverse environment.